Effective “off-on” switch for fertility control in female zebrafish - Shi, Shengchi; Zhang, Yuqing; Huang, Jianfei; Lou, Qiyong; Jin, Xia; He, Jiangyan; Zhai, Gang; Yin, Zhan (Frontiers in Marine Science, 2024)
The implementation of a controllable sterility strategy is crucial for the commercialization of precise trait improvements in farmed fish using genome editing and sustainable development of fisheries. Our previous research has demonstrated that females deficient in pituitary gonadotropin luteinizing hormone β-subunit (lhβ) or gonadal steroidogenesis gene steroidogenic acute regulatory protein (star) exhibit sterility due to impaired oocyte maturation and ovulation. Nevertheless, the effective restoration of fertility in lhβ- or star-deficient females remains unsolved. This study has discovered that the administration of exogenous 17α,20β-dihydroxy-4-pregnen-3-one (DHP) at 100 and 300 μg/L for 6 h (from 02:00 to 08:00 a.m.) effectively restores the fertility of lhβ- or star-deficient females. Fertilized eggs from these mutant females can be raised without noticeable developmental defects for up to 3 weeks post-fertilization (wpf) compared to the wild-type (WT) control zebrafish. The increased expression levels of adamts9 and adam8b in lhβ- or star-deficient zebrafish females treated with DHP demonstrate a positive correlation with oocyte maturation and ovulation restoration. In contrast, exogenous DHP administration did not rescue the sterility phenotype observed in progesterone receptor (pgr)-deficient females. Building on our recent success in generating an all-female carp population through cytochrome P450, family 17, subfamily A, polypeptide 1 (cyp17a1)-depletion, our research presents a promising and effective strategy for an “off-on” switch for managing fertility in genome-edited cyprinids. The strategy would offer practical guidance and theoretical justification for developing “controllable fertility” in all-female fish, which would support the sustainable development of fisheries by promoting the use of novel biotechnologies in aquaculture in an eco-friendly manner.